2021
DOI: 10.1097/mpa.0000000000001935
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging–Based Radiomics Models to Predict Early Extrapancreatic Necrosis in Acute Pancreatitis

Abstract: The aim of the study was to investigate radiomics models based on magnetic resonance imaging (MRI) for predicting early extrapancreatic necrosis (EXPN) in acute pancreatitis.Methods: Radiomics features were extracted from T2-weighted images of extrapancreatic collections and late arterial-phase images of the pancreatic parenchyma for 135 enrolled patients (94 in the primary cohort, including 47 EXPN patients and 41 in the validation cohort, including 20 EXPN patients). The optimal features after dimension redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The conventional imaging features usually lag behind disease progression, which cannot help clinical decision-making. Current studies demonstrated the usefulness of radiomics in predicting severity, recurrence, progression, and extra-pancreatic necrosis [ 33 , 35 , 40 , 41 , 45 , 59 ]. However, the studies were conducted by varying imaging modalities concerning separate outcomes, which do not allow further meta-analysis to establish any evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional imaging features usually lag behind disease progression, which cannot help clinical decision-making. Current studies demonstrated the usefulness of radiomics in predicting severity, recurrence, progression, and extra-pancreatic necrosis [ 33 , 35 , 40 , 41 , 45 , 59 ]. However, the studies were conducted by varying imaging modalities concerning separate outcomes, which do not allow further meta-analysis to establish any evidence.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that anatomically, the lymphatic plexus around the transverse septum is connected with the mediastinal and subcostal spaces, the giant inflammatory cells formed by AP spread into the mediastinum and subcostal space through the lymph plexus around the septum, and the pancreatic enzyme effusion containing soluble tissue gradually entered the chest cavity. PE is important for assessing the severity and prognosis of AP and is the main symptom of extrapancreatic involvement of AP [ 29 ]. Although PE can also be detected radiologically early, most of them occur earlier than the date of pancreatic injury, and the incidence of PE increases with increasing CTSI score [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al ( 20 ) used an MRI based radiomics model to predict early extrapancreatic necrosis (EXPN) in patients with AP. They enrolled 135 AP patients who were divided into the training ( n = 94, with 47 EXPN and 47 APFC patients) and validation cohorts ( n = 41, with 20 EXPN and 21 APFC patients).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…They enrolled 135 AP patients who were divided into the training ( n = 94, with 47 EXPN and 47 APFC patients) and validation cohorts ( n = 41, with 20 EXPN and 21 APFC patients). On the T2WI and late arterial phase images, Zhou et al ( 20 ) extracted 350 image radiomics features from ROI of the peripancreatic collections (T2WI) and entire pancreatic parenchyma (late arterial phase). After dimension reduction and feature selection, 22 features (12 from the T2WI and 10 from the late arterial phase images) were selected for establishing SVM model.…”
Section: Clinical Applicationsmentioning
confidence: 99%